Polyimide Dendrimers Containing Multiple Electron Donor–Acceptor Units and Their Unique Photophysical Properties1. Issue 23 (27th April 2015) - Toma, Francesca M.; Puntoriero, Fausto; Pho, Toan V.; La Rosa, Marcello; Jun, Young‐Si; Tremolet de Villers, Bertrand J.; Pavlovich, James; Stucky, Galen D.; Campagna, Sebastiano; Wudl, Fred
Abstract: A high‐yielding synthesis of a series of polyimide dendrimers, including decacyclene‐ and perylene‐containing dendrimerD6, in which two types of polyimide dyes are present, is reported. In these constructs, the branching unit is represented by trisphenylamine, and the solubilizing chains by N ‐9‐heptadecanyl‐substituted perylene diimides. The photophysical properties of the dendrimers have been studied by absorption, steady‐state, and time‐resolved emission spectroscopy and pump–probe transient absorption spectroscopy. Photoinduced charge‐separated (CS) states are formed on the femtosecond timescale upon visible excitation. In particular, inD6, two different CS states can be formed, involving different subunits that decays independently with different lifetimes (ca. 10–100 ps). Abstract : Quick as a flash : New polyimide dendrimers exhibiting rich photophysical properties have been synthesized. For example, in one of the new species, two different charge‐separated states can be obtained on the femtosecond timescale. Such charge‐separated states independently decay on the picosecond timescale.